2003
DOI: 10.1007/s00415-003-0976-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in spinocerebellar ataxia type 1, 2, and 3

Abstract: Cognitive impairment was studied in distinct types of spinocerebellar ataxia (SCA): eleven SCA1, 14 SCA2, and 11 SCA3 individuals and 8 age- and IQ- matched controls. All were submitted to a neuropsychological test battery that comprised tests for IQ, attention, executive function, verbal and visuospatial memory. Executive dysfunction was prominent in SCA1 as compared with controls and all other SCA types. Mild deficits of verbal memory were present in SCA1, SCA2 and SCA3. The neuropathological pattern in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
165
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(183 citation statements)
references
References 35 publications
14
165
1
3
Order By: Relevance
“…In this regard, the cognitive phenotype of FXTAS is similar to that of several of the spinocerebellar ataxias, the frontal variant of frontotemporal dementia, Parkinson disease, multiple system atrophy, and other subcortical dementias (e.g., Bak, Crawford, Hearn, Mathuranath, & Hodges, 2005;Burk et al, 2003;Dubois & Pillon, 2002;Kertesz, McMonagle, Blair, Davidson, & Munoz, 2005;Liu et al, 2004;McKhann et al, 2001;O'Hearn, Holmes, Calvert, Ross, & Margolis, 2001;Robbins et al, 1992;Schelhaas & van de Warrenburg, 2005). Viewed from the perspective of Fuster's model of executive functioning, FXTAS is marked especially by deficits in behavioral self-regulation (including disinhibition), working memory, and control of attention.…”
Section: Contribution Of Ecf Deficits To Impairment In Non-executive mentioning
confidence: 92%
“…In this regard, the cognitive phenotype of FXTAS is similar to that of several of the spinocerebellar ataxias, the frontal variant of frontotemporal dementia, Parkinson disease, multiple system atrophy, and other subcortical dementias (e.g., Bak, Crawford, Hearn, Mathuranath, & Hodges, 2005;Burk et al, 2003;Dubois & Pillon, 2002;Kertesz, McMonagle, Blair, Davidson, & Munoz, 2005;Liu et al, 2004;McKhann et al, 2001;O'Hearn, Holmes, Calvert, Ross, & Margolis, 2001;Robbins et al, 1992;Schelhaas & van de Warrenburg, 2005). Viewed from the perspective of Fuster's model of executive functioning, FXTAS is marked especially by deficits in behavioral self-regulation (including disinhibition), working memory, and control of attention.…”
Section: Contribution Of Ecf Deficits To Impairment In Non-executive mentioning
confidence: 92%
“…For instance, Bürk et al (1999) found that even the demented subset of their German spinocerebellar ataxia (SCA) 2 patients was only slightly lowered (4.8 +/− 1) relative to the controls (6.1 +/− 1), whereas their non-demented SCA2 patients did not differ significantly from controls (5.9 +/− 1.3). Other studies have similarly reported digit spans in the low-normal to normal range with no statistical differences between patients and controls (e.g., Bracke-Tolkmitt et al, 1989;Fiez et al, 1992;Schmahmann & Sherman, 1998;Le Pira et al, 2002;Timmann et al, 2002;Bürk et al, 2003;Globas et al, 2003;Fabbro et al, 2004). Those studies that have reported digit spans to be reduced (e.g., Akshoomoff et al, 1992;Schelhaas et al, 2001), even when significantly reduced relative to controls (e.g., Witt et al, 2002; Ravizza et al, 2004, submitted; Maddox et al., in press), typically report a reduction of only one or two items from the normal range.…”
mentioning
confidence: 88%
“…Test performance was not related to either trinucleotide repeat length or disease duration. A comparison of cognitive dysfunction among SCA1, SCA2 and SCA3 patients revealed that executive dysfunction was more prominent in SCA1 patients compared with other SCA types [12]. It was also reported that depressive and memory symptoms were found in 25 and 42% of SCA1 patients, respectively [13].…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%